Preparation of roasted ternary layered double hydroxide with enhanced adsorption performance and application of roasted ternary layered double hydroxide in low-concentration bromide ion adsorption
By introducing cobalt elements into layered magnesium hydroxide and calcining, a ternary layered double hydroxide with high efficiency adsorption and structural memory effects was prepared, which solved the problem of low adsorption rate of bromide ion in existing materials. It realizes efficient adsorption and recycling, and is suitable for industrial applications.
Patent Information
- Application Number
- CN202411622387.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-10
AI Technical Summary
The existing calcined layered double hydroxide materials have low adsorption rate of low-concentration bromide ion, and it is difficult to achieve efficient recycling and reuse.
Cobalt elements are introduced into layered magnesium hydroxide aluminum, ternary layered hydroxide is prepared by co-precipitation method, and roasted at high temperature to form calcined ternary layered double hydroxide with structural memory effect, thereby improving its adsorption Capacity and reuse capability.
It achieves efficient adsorption of low-concentration bromide ions, with an adsorption capacity of 158.5 mg/g, and has the characteristics of recycling and reuse after calcination, simplifying the material preparation process and suitable for large-scale industrial production.
Smart Images

Figure CN119281290A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of adsorption materials, and in particular relates to the preparation of a calcined ternary layered double hydroxide with enhanced adsorption performance and its application in the adsorption of low-concentration bromide ions. Background Art
[0002] Bromine is a valuable halogen element that plays a key role as a chemical raw material in many industries such as fungicides, flame retardants and rubber manufacturing. Bromide mainly exists in seawater, oilfield water, salt lakes and underground brines in ionic form. The continued sustainable development of global industry has promoted a significant increase in the demand for bromine. Therefore, it is urgent to accelerate the development of cost-effective, direct and reliable bromide ion extraction technology to meet the actual needs of contemporary industrial manufacturing. Traditional technologies for bromine extraction include air blowing, ion exchange and membrane separation, but these methods have limitations such as excessive energy consumption, high investment cost and low efficiency. In recent years, adsorption method has been widely used due to its inherent advantages in economic feasibility, simplicity and reduction of secondary pollution.
[0003] Layered double hydroxides (LDHs), also known as hydrotalcites, are a new type of inorganic functional materials with a layered structure. They are widely used in adsorption, catalysis, energy storage, biology, drug release, heavy metal ion adsorption and other fields. The emerging ternary LDHs also show broad application prospects in the field of adsorption. The adsorption performance of the material can be further improved by precisely controlling its composition and structure. In addition, the calcined LDH can undergo a structural transformation and be converted into a metal oxide with thermal and chemical stability. After calcination, most of the anions between the layers are eliminated, and then when hydrated again, the anions in the water are inserted into the layers, and the original layered structure can be restored. This property is called the "structural memory effect". The calcined LDH is a good bromide ion adsorption material. It can not only adsorb bromide ions under low concentration conditions, but also can be repeatedly recycled and reused due to its structural memory characteristics. Summary of the invention
[0004] In view of the problem that the current calcined layered double hydroxide material has a low adsorption rate for low-concentration bromide ions, the present invention provides a calcined ternary layered double hydroxide with enhanced adsorption performance and its application in low-concentration bromide ion adsorption. The present invention introduces cobalt elements into the layered magnesium aluminum hydroxide to increase the adsorption capacity of the adsorbent material, and the adsorbent can also be recycled and reused, so it is a highly efficient bromide ion adsorbent.
[0005] The method for preparing a calcined ternary layered double hydroxide having enhanced adsorption performance of the present invention comprises the following steps: Step 1: Take a certain amount of magnesium salt and aluminum salt and mix them to prepare solution A; take a certain amount of sodium salt and prepare it to prepare solution B; mix solution A and solution B by dropping, and control the pH of the mixed suspension within a certain range. After the dropping is completed, age the suspension at a certain temperature for a period of time, then filter and wash to neutrality, and dry (dry at 80°C for 24 hours) to obtain layered magnesium aluminum hydroxide; Step 2: Take a certain amount of cobalt salt and a certain amount of imidazole and add them to a certain amount of solvent, stir for a period of time, and then stand at a certain temperature for a period of time to finally obtain a precipitate. The precipitate is centrifuged, washed and dried to finally obtain ZIF-67.
[0006] Step 3: Add the layered magnesium aluminum hydroxide prepared in step 1 and the ZIF-67 prepared in step 2 to a certain amount of solvent, react the mixture in a reactor at high temperature for a period of time, and naturally cool it to room temperature to finally obtain a flaky ternary layered hydroxide. Put the prepared layered hydroxide into a muffle furnace for roasting, and naturally cool it to room temperature after roasting to obtain a roasted ternary layered double hydroxide.
[0007] in: In step 1, the magnesium salt is magnesium nitrate hexahydrate; the aluminum salt is aluminum nitrate nonahydrate; and the solvent used to prepare solution A is deionized water.
[0008] The sodium salt is a mixture of sodium hydroxide and anhydrous sodium carbonate, and the solvent used to prepare solution B is deionized water.
[0009] Further, the mass ratio of sodium hydroxide to sodium carbonate is controlled to be 2:1.
[0010] The pH value of the mixed suspension is controlled at 9-10.
[0011] The aging temperature is 65°C and the time is 16 hours.
[0012] In step 2, the cobalt salt is Co (NO3)2·6H2O, the imidazole is 2-methylimidazole, and the solvent is methanol.
[0013] Furthermore, the molar ratio of magnesium, aluminum and cobalt is controlled to be 5:2:1.
[0014] Furthermore, the molar ratio of the cobalt salt to the imidazole is controlled to be 1:6.
[0015] The stirring and standing temperature is 25°C, the stirring time is 30 min, the standing time is 24 h, the drying temperature is 60°C, and the drying time is 24 h.
[0016] In step 3, the solvent is deionized water, the reaction temperature is 120° C., the reaction time is 12 h, and the mass ratio of ZIF-67, layered magnesium aluminum hydroxide and the solvent is controlled to be 1:6:50.
[0017] The calcination was carried out in an air atmosphere at a temperature of 500°C and a time of 5 h.
[0018] The calcined ternary layered double hydroxide prepared by the invention is used as an adsorption material in the adsorption of bromide ions.
[0019] The beneficial effects of the present invention are embodied in: 1. The adsorption capacity of the calcined layered magnesium aluminum hydroxide of the present invention for low concentration bromide ions (<100 ppm) can reach 158.5 mg / g, which is the best adsorption effect among the LDH materials reported so far.
[0020] 2. Due to the shape memory properties of calcined layered magnesium aluminum hydroxide, it has a good adsorption effect on low-concentration bromide ions, and can be recovered and reused by calcination after adsorption.
[0021] 3. The preparation process of this material is relatively simple, and it is promising to realize batch preparation and industrial large-scale production of adsorbents. This material provides an efficient and significant method for the adsorption of low-concentration bromide ions in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.
[0023] Figure 1 This is the XRD spectrum of ZIF-67. From the peak shape in the figure, it can be seen that ZIF-67 was successfully synthesized.
[0024] Figure 2 The XRD spectra of ternary layered double hydroxide and calcined ternary layered double hydroxide are shown in Figure 2. Figure 2 It can be seen that the crystal structure of layered magnesium aluminum hydroxide was synthesized by co-precipitation method, and after calcination at 500°C, the characteristic peaks of layered magnesium aluminum hydroxide disappeared, showing the characteristic peaks of magnesium oxide and aluminum oxide.
[0025] Figure 3 It is the mass loss rate and mass loss rate spectrum of ternary layered double hydroxide. Figure 3 It can be seen that the thermal weight loss process of ternary layered double hydroxide is divided into two stages. The first stage is the loss of crystal water, and the second stage is the removal of hydroxyl groups in the layer plates and interlayer carbonate groups, and the layered structure is destroyed.
[0026] Figure 4 This is the infrared spectrum of the calcined ternary layered double hydroxide. Figure 3 It can be seen that the absorption vibration peak of carbonate disappears, indicating that carbonate is basically removed during the roasting process.
[0027] Figure 5 is the SEM image of ZIF-67. Figure 5 It can be seen that ZIF-67 presents an octahedral morphology.
[0028] Figure 6 This is a SEM image of layered magnesium aluminum hydroxide. Figure 6 It can be seen that the layered magnesium aluminum double hydroxide presents a nanoflower morphology.
[0029] Figure 7 This is a SEM image of a ternary layered double hydroxide. Figure 7 It can be seen that the ternary layered double hydroxide presents an irregular hexagonal nanosheet morphology.
[0030] Figure 8 This is a SEM image of a calcined ternary layered double hydroxide with a magnesium-aluminum-cobalt ratio of 5:2:0.5. Figure 8 It can be seen that after calcination, the flaky structure is partially destroyed.
[0031] Fig. 9 This is a SEM image of a calcined ternary layered double hydroxide with a magnesium-aluminum-cobalt ratio of 5:2:0.75. Fig. 9 It can be seen that when the proportion of cobalt increases, the calcined material becomes more dispersed and the surface becomes rough.
[0032] Fig.10 This is a SEM image of a calcined ternary layered double hydroxide with a magnesium-aluminum-cobalt ratio of 5:2:1. Fig.10 It can be seen that when the proportion of cobalt continues to increase, the material completely loses its flaky structure and the morphology becomes irregular.
[0033] Fig.11 This is the mapping+EDS image of calcined layered magnesium aluminum hydroxide. Fig.11 It can be seen that the elements of the calcined ternary layered double hydroxide are evenly distributed, and the mass ratio of Mg:Al:Co elements is approximately 8:4:4, and the amount ratio is 5:2:1.
[0034] Fig.12 This is a graph showing the change in the adsorption rate of aluminum on calcined layered magnesium hydroxide over time. Fig.12 It can be seen that calcined ternary layered double hydroxide can achieve rapid adsorption of bromide ions within 40 min. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with examples. The specific examples described here are only used to explain the present invention and do not limit the present invention. Embodiment 1:
[0036] The calcined layered hydroxide is prepared by calcining the layered hydroxide prepared by the coprecipitation method at a high temperature. The preparation method is as follows: 1. According to nMg / nAl=2.5, weigh 25.6 g of Mg (NO3)2·6H2O and 15.6 g of Al(NO3)3·9H2O, mix and add to 100 mL of deionized water to prepare a mixed salt solution, called solution A; weigh 9.6 g of NaOH and 5.0 g of Na2CO3, mix and add to 100 mL of deionized water to prepare a precipitant, called solution B. Slowly drop solution A and solution B into a three-necked flask at the same time and stir continuously, control the pH of the system between 9 and 10, and obtain a white suspension. After the addition is completed, the white suspension is aged at 65°C for 16 h, then filtered, and the filtrate is washed with deionized water until the filtrate is neutral. Finally, the filter cake is dried at 80°C for 24 h to obtain a layered magnesium aluminum hydroxide sample.
[0037] 2. According to the molar ratio of 2-methylimidazole to Co (NO3)2·6H2O of 6:1, weigh 0.485 g of Co (NO3)2·6H2O and 0.82 g of 2-methylimidazole, mix and add to 50 ml of methanol solution, stir at 25°C for 30 min, then stand at 25°C for 24 h, finally centrifuge and wash with methanol, and dry in a vacuum oven at 60°C for 12 h to obtain ZIF-67.
[0038] 3. Weigh 1.0 g of the layered magnesium aluminum hydroxide obtained in step 1 and 0.15 g of the ZIF-67 obtained in step 2, add them into 50 ml of deionized water, stir and mix them evenly, then transfer them to a reactor, react at 120°C for 12 h, cool naturally to room temperature, then wash with deionized water by centrifugation, and finally dry at 60°C under vacuum for 24 h to obtain the ternary layered hydroxide CoMgAl-LDH.
[0039] 4. The layered magnesium aluminum cobalt hydroxide obtained by drying in step 3 is placed in a muffle furnace, calcined at 500°C for 5 hours, and naturally cooled to room temperature to obtain calcined layered hydroxide CoMgAl-LDH ( Fig.10 ).
[0040] The CoMgAl-LDH prepared in this example has basically no hexagonal sheet structure, its dispersibility is increased, its size is reduced, and its surface is relatively rough. 50 mg of the calcined layered magnesium aluminum hydroxide prepared in this example was added to 100 mL of a 100 ppm potassium bromide solution, the adsorption temperature was 30°C, the adsorption time was 40 min, and the adsorption capacity was 158.5 mg / g. Embodiment 2:
[0041] The calcined layered hydroxide is prepared by calcining the layered hydroxide prepared by the coprecipitation method at a high temperature. The preparation method is as follows: 1. According to nMg / nAl=2.5, weigh 25.6 g of Mg (NO3)2·6H2O and 15.6 g of Al(NO3)3·9H2O, mix and add to 100 mL of deionized water to prepare a mixed salt solution, called solution A; weigh 9.6 g of NaOH and 5.0 g of Na2CO3, mix and add to 100 mL of deionized water to prepare a precipitant, called solution B. Slowly drop solution A and solution B into a three-necked flask at the same time and stir continuously, control the pH of the system between 9 and 10, and obtain a white suspension. After the addition is completed, the white suspension is aged at 65°C for 16 h, then filtered, and the filtrate is washed with deionized water until the filtrate is neutral. Finally, the filter cake is dried at 80°C for 24 h to obtain a layered magnesium aluminum hydroxide sample.
[0042] 2. The layered magnesium aluminum hydroxide obtained by drying in step 1 is placed in a muffle furnace, calcined at 500° C. for 5 h, and naturally cooled to room temperature to obtain calcined layered hydroxide MgAl-LDH.
[0043] 50 mg of the calcined layered magnesium aluminum hydroxide prepared in this example was added to 100 mL of a potassium bromide solution having a concentration of 100 ppm. The adsorption temperature was 30° C., the adsorption time was 12 h, and the adsorption capacity was 97.12 mg / g. Embodiment 3:
[0044] 1. According to nMg / nAl=2.5, weigh 25.6 g of Mg (NO3)2·6H2O and 15.6 g of Al(NO3)3·9H2O, mix and add to 100 mL of deionized water to prepare a mixed salt solution, called solution A; weigh 9.6 g of NaOH and 5.0 g of Na2CO3, mix and add to 100 mL of deionized water to prepare a precipitant, called solution B. Slowly drop solution A and solution B into a three-necked flask at the same time and stir continuously, control the pH of the system between 9 and 10, and obtain a white suspension. After the addition is completed, the white suspension is aged at 65°C for 16 h, then filtered, and the filtrate is washed with deionized water until the filtrate is neutral. Finally, the filter cake is dried at 80°C for 24 h to obtain a layered magnesium aluminum hydroxide sample.
[0045] 2. According to the molar ratio of 2-methylimidazole to Co (NO3)2·6H2O of 6:1, weigh 0.485 g of Co (NO3)2·6H2O and 0.82 g of 2-methylimidazole, mix and add to 50 ml of methanol solution, stir at 25°C for 30 min, then stand at 25°C for 24 h, finally centrifuge and wash with methanol, and dry in a vacuum oven at 60°C for 12 h to obtain ZIF-67.
[0046] 3. Weigh 1.0 g of the layered magnesium aluminum hydroxide obtained in step 1 and 0.05 g of ZIF-67 obtained in step 2, add them into 50 ml of deionized water, stir and mix them evenly, then transfer them to a reactor, react at 120 ° C for 12 h, cool naturally to room temperature, then centrifuge and wash with deionized water, and finally dry them at 60 ° C under vacuum conditions for 24 h to obtain the ternary layered hydroxide CoMgAl-LDH.
[0047] 4. The layered magnesium aluminum cobalt hydroxide obtained by drying in step 3 is placed in a muffle furnace, calcined at 500° C. for 5 h, and naturally cooled to room temperature to obtain calcined layered hydroxide CoMgAl-LDH.
[0048] By reducing the amount of cobalt added, the calcined layered hydroxide CoMgAl-LDH prepared is larger in size and more regular in morphology than that in Example 1, but with slightly worse dispersion, and is mostly in block form ( Figure 8 ) The adsorption capacity decreased. 50 mg of the calcined layered hydroxide CoMgAl-LDH prepared in this example was added to 100 mL of a 100 ppm potassium bromide solution. The adsorption temperature was 30°C, the adsorption time was 40 min, and the adsorption capacity was 102.2 mg / g. Embodiment 4:
[0049] 1. According to nMg / nAl=2.5, weigh 25.6 g of Mg (NO3)2·6H2O and 15.6 g of Al(NO3)3·9H2O, mix and add to 100 mL of deionized water to prepare a mixed salt solution, called solution A; weigh 9.6 g of NaOH and 5.0 g of Na2CO3, mix and add to 100 mL of deionized water to prepare a precipitant, called solution B. Slowly drop solution A and solution B into a three-necked flask at the same time and stir continuously, control the pH of the system between 9 and 10, and obtain a white suspension. After the addition is completed, the white suspension is aged at 65°C for 16 h, then filtered, and the filtrate is washed with deionized water until the filtrate is neutral. Finally, the filter cake is dried at 80°C for 24 h to obtain a layered magnesium aluminum hydroxide sample.
[0050] 2. According to the molar ratio of 2-methylimidazole to Co (NO3)2·6H2O of 6:1, weigh 0.485 g of Co (NO3)2·6H2O and 0.82 g of 2-methylimidazole, mix and add to 50 ml of methanol solution, stir at 25°C for 30 min, then stand at 25°C for 24 h, finally centrifuge and wash with methanol, and dry in a vacuum oven at 60°C for 12 h to obtain ZIF-67.
[0051] 3. Weigh 1.0 g of the layered magnesium aluminum hydroxide obtained in step 1 and 0.10 g of the ZIF-67 obtained in step 2, add them into 50 ml of deionized water, stir and mix them evenly, then transfer them to a reactor, react at 120 ° C for 12 h, cool naturally to room temperature, then centrifuge and wash with deionized water, and finally dry them at 60 ° C under vacuum for 24 h to obtain the ternary layered hydroxide CoMgAl-LDH.
[0052] 4. The layered magnesium aluminum cobalt hydroxide obtained by drying in step 3 is placed in a muffle furnace, calcined at 500° C. for 5 h, and naturally cooled to room temperature to obtain calcined layered hydroxide CoMgAl-LDH.
[0053] By slightly increasing the amount of cobalt added, the calcined layered hydroxide CoMgAl-LDH prepared is smaller in size, more irregular in morphology, and has better dispersion than that in Example 3 ( Fig.10 ) The adsorption capacity increased slightly, but not as good as Example 1. 50 mg of the calcined layered magnesium aluminum hydroxide prepared in this example was added to 100 mL of a 100 ppm potassium bromide solution, the adsorption temperature was 30°C, the adsorption time was 40 min, the adsorption rate was 82%, and the adsorption capacity was 118.2 mg / g. Embodiment 5:
[0054] The calcined layered hydroxide is prepared by calcining the layered hydroxide prepared by the coprecipitation method at a high temperature. The preparation method is as follows: 1. According to nMg / nAl=2.5, weigh 25.6 g of Mg (NO3)2·6H2O and 15.6 g of Al(NO3)3·9H2O, mix and add to 100 mL of deionized water to prepare a mixed salt solution, called solution A; weigh 9.6 g of NaOH and 5.0 g of Na2CO3, mix and add to 100 mL of deionized water to prepare a precipitant, called solution B. Slowly drop solution A and solution B into a three-necked flask at the same time and stir continuously, control the pH of the system between 9 and 10, and obtain a white suspension. After the addition is completed, the white suspension is aged at 65°C for 16 h, then filtered, and the filtrate is washed with deionized water until the filtrate is neutral. Finally, the filter cake is dried at 80°C for 24 h to obtain a layered magnesium aluminum hydroxide sample.
[0055] 2. According to the molar ratio of 2-methylimidazole to Co (NO3)2·6H2O of 6:1, weigh 0.485 g of Co (NO3)2·6H2O and 0.82 g of 2-methylimidazole, mix and add to 50 ml of methanol solution, stir at 25°C for 30 min, then stand at 25°C for 24 h, finally centrifuge and wash with methanol, and dry in a vacuum oven at 60°C for 12 h to obtain ZIF-67.
[0056] 3. Weigh 1.0 g of the layered magnesium aluminum hydroxide obtained in step 1 and 0.15 g of the ZIF-67 obtained in step 2, add them into 50 ml of deionized water, stir and mix them evenly, then transfer them to a reactor, react at 120 ° C for 12 h, cool naturally to room temperature, then centrifuge and wash with deionized water, and finally dry them at 60 ° C under vacuum for 24 h to obtain the ternary layered hydroxide CoMgAl-LDH.
[0057] 4. The layered magnesium aluminum cobalt hydroxide obtained by drying in step 3 is placed in a muffle furnace, calcined at 500° C. for 4 hours, and naturally cooled to room temperature to obtain calcined layered hydroxide CoMgAl-LDH.
[0058] 50 mg of the calcined layered magnesium aluminum hydroxide prepared in this example was added to 100 ml of a potassium bromide solution with a concentration of 100 ppm. The adsorption temperature was 30°C, the adsorption time was 40 min, and the adsorption capacity was 128.6 mg / g, indicating that the calcination time would have a certain degree of influence on the adsorption capacity. When the calcination time was too short, the interlayer anions were not completely removed, resulting in a decrease in the adsorption capacity for bromide ions. Embodiment 6:
[0059] The calcined layered hydroxide is prepared by calcining the layered hydroxide prepared by the coprecipitation method at a high temperature. The preparation method is as follows: 1. According to nMg / nAl=2.5, weigh 25.6 g of Mg (NO3)2·6H2O and 15.6 g of Al(NO3)3·9H2O, mix and add to 100 mL of deionized water to prepare a mixed salt solution, called solution A; weigh 9.6 g of NaOH and 5.0 g of Na2CO3, mix and add to 100 mL of deionized water to prepare a precipitant, called solution B. Slowly drop solution A and solution B into a three-necked flask at the same time and stir continuously, control the pH of the system between 9 and 10, and obtain a white suspension. After the addition is completed, the white suspension is aged at 65°C for 16 h, then filtered, and the filtrate is washed with deionized water until the filtrate is neutral. Finally, the filter cake is dried at 80°C for 24 h to obtain a layered magnesium aluminum hydroxide sample.
[0060] 2. According to the molar ratio of 2-methylimidazole to Co (NO3)2·6H2O of 6:1, weigh 0.485 g of Co (NO3)2·6H2O and 0.82 g of 2-methylimidazole, mix and add to 50 ml of methanol solution, stir at 25°C for 30 min, then stand at 25°C for 24 h, finally centrifuge and wash with methanol, and dry in a vacuum oven at 60°C for 12 h to obtain ZIF-67.
[0061] 3. Weigh 1.0 g of the layered magnesium aluminum hydroxide obtained in step 1 and 0.15 g of the ZIF-67 obtained in step 2, add them into 50 ml of deionized water, stir and mix them evenly, then transfer them to a reactor, react at 120 ° C for 12 h, cool naturally to room temperature, then centrifuge and wash with deionized water, and finally dry them at 60 ° C under vacuum for 24 h to obtain the ternary layered hydroxide CoMgAl-LDH.
[0062] 4. The layered magnesium aluminum cobalt hydroxide obtained by drying in step 3 is placed in a muffle furnace, calcined at 500° C. for 6 hours, and naturally cooled to room temperature to obtain calcined layered hydroxide CoMgAl-LDH.
[0063] 50 mg of the calcined layered magnesium aluminum hydroxide prepared in this example was added to 100 mL of a potassium bromide solution with a concentration of 100 ppm. The adsorption temperature was 30°C, the adsorption time was 40 min, and the adsorption capacity was 154.6 mg / g. Prolonging the calcination time did not cause a further increase in the adsorption capacity, indicating that the optimal calcination time was reached at 500°C for 5 hours.
Claims
1. A method for preparing a calcined ternary layered double hydroxide having enhanced adsorption properties, characterized in that The steps include: Step 1: Mix magnesium salt and aluminum salt to prepare solution A; prepare sodium salt to prepare solution B; mix solution A and solution B by dropwise addition, and control the pH of the mixed suspension within a certain range. After the dropwise addition is completed, age the suspension at a certain temperature for a period of time, filter and wash to neutrality, and dry to obtain layered magnesium aluminum hydroxide; Step 2: Add a certain amount of cobalt salt and a certain amount of imidazole to a certain amount of solvent, stir for a period of time, and then stand at a certain temperature for a period of time to obtain a precipitate, centrifuge, wash and dry the precipitate to obtain ZIF-67; Step 3: Add the layered magnesium aluminum hydroxide prepared in step 1 and the ZIF-67 prepared in step 2 to a certain amount of solvent, react the mixture in a reactor at high temperature for a period of time, and naturally cool it to room temperature to finally obtain a flaky ternary layered hydroxide. Put the prepared layered hydroxide into a muffle furnace for roasting, and naturally cool it to room temperature after roasting to obtain a roasted ternary layered double hydroxide.
2. The preparation method according to claim 1, characterized in that: In step 1, the magnesium salt is magnesium nitrate hexahydrate; and the aluminum salt is aluminum nitrate nonahydrate.
3. The preparation method according to claim 1, characterized in that: In step 1, the sodium salt is a mixture of sodium hydroxide and anhydrous sodium carbonate, and the mass ratio of sodium hydroxide to sodium carbonate is controlled to be 2:
1.
4. The preparation method according to claim 1, characterized in that: In step 1, the pH value of the mixed suspension is controlled at 9-10.
5. The preparation method according to claim 1, characterized in that: In step 1, the aging temperature is 65° C. and the time is 16 h.
6. The preparation method according to claim 1, characterized in that: In step 2, the cobalt salt is Co (NO3)2·6H2O, the imidazole is 2-methylimidazole, and the solvent is methanol.
7. The preparation method according to claim 6, characterized in that: The molar ratio of cobalt salt to imidazole is 1:
6.
8. The preparation method according to claim 1, characterized in that: The amount ratio of magnesium, aluminum and cobalt is controlled to be 5:2:
1.
9. The preparation method according to claim 1, characterized in that: In step 3, calcination is carried out in an air atmosphere at a temperature of 500° C. for 5 hours.
10. Use of the calcined ternary layered double hydroxide prepared by the preparation method according to any one of claims 1 to 9 as an adsorption material in the adsorption of low-concentration bromide ions.